PENDAMPINGAN HUKUM CUMA-CUMA DI PERSIDANGAN PENGADILAN NEGERI JAKARTA BARAT BAGI WARGA BINAAN RUMAH TAHAN KELAS I SALEMBA - Hery Firmansyah; Amad Sudiro; Sindhi Cintya; Charina Putri Besila (PROSIDING SERINA, 2021)
Legal aid is also a legal service to provide legal protection and defense of the human rights of a suspect or defendant from the time he is detained until a permanent court decision is obtained. The suspect or defendant who is defended and given legal protection is not the fault of the suspect/defendant but the human rights of the suspect/defendant to avoid being treated and acted inappropriately or arbitrarily by law enforcement officials. Legal aid is also a service provided by legal aid providers. Legal assistance is expected to provide input for the community, especially residents of the Salemba Class I Detention Center in providing assistance, defense, and other legal actions for the client's legal interests. Legal assistance will be carried out at the West Jakarta District Court, the collaboration between Lecturers and Lawyers is to increase the sense of justice for justice seekers, especially inmates from the Salemba Class I Detention Center. For administrative matters, the trial requirements will be handled by students starting from the collection of a Certificate of Incapacity (SKTM) and the identity of the defendant issued from the Salemba Rutan. Legal Aid is a legal service provided by Advocates free of charge to clients who cannot afford it. Legal aid itself can be in the form of services provided by advocates in the form of providing legal consultation, legal assistance, exercising power of attorney, representing, assisting, defending, and taking other legal actions for the legal interests of clients.